Preparation and investigation of high-temperature proton exchange membranes based on phosphoric acid doped imidazolium polysilsesquioxane crosslinked poly(vinyl chloride) - Yaping Jin; Chao Liu; Ruihong Liu; Xuefu Che; Jingshuai Yang (eXPRESS Polymer Letters)
Developing high-performance and low-cost polymer membranes for high-temperature proton exchange membrane fuel cells is a big challenge to the polymer design. Herein, high-temperature proton exchange membranes are prepared based on the low-cost thermoplastic resin of poly(vinyl chloride) (PVC). However, the methylimidazolium PVC exhibits significantly low phosphoric acid (PA) doping content and low conductivity due to the compact structure. Thus, the N-[3-(triethoxysilyl) propyl]-4,5-dihydroimidazole (SiIm) is employed as a dual functionalized reagent for PVC. On the one hand, SiIm is used to quaternize PVC through the SN2 nucleophilic substitution between chloride and imidazole. On the other hand, the crosslinked siloxane network is formed via the hydrolysis reaction of SiIm in a dilute sulfuric acid solution. The obtained polysilsesquioxane crosslinked membranes (PVC-x%SiIm) display good thermal stability, excellent PA doping ability, superior proton conductivity, and moderate tensile strength. For instance, the PVC-17%SiIm membrane achieves a high PA doping content of 243% after immersing in 85 wt% PA solution and exhibits the highest conductivity of 0.111 S·cm–1 at 180 °C without humidifying and tensile strength of 6.0 MPa at room temperature.